IMPROVING THE ABILITY OF STUDENTS IN WRITING DESCRIPTIVE TEXT BY USING MIND MAPPING - Cut Indah Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2020)
The objective of this research was to find out is there any differences between the students who are tought by using mind mapping technique and the students who are tought by using conventional technique to improve the ability in writing descriptive text. The sample of this research ware the second year students of SMA 2 Indrajaya class XI IPA as experimental class and XI IPS as control class. Each classes consist of 23 students. to collect the data in this quantitative researcher, the researcher used a set of written test. The reaearcher used an analytic scoring to score the students’ writing on the pre-test and post-test to attain the reliability of the instrument. The result of students’ pre-test mean score in the experimental class was 58,86 while the students’ post-test mean score was 68, and the different mean score with t-test is 16,90. The students pre-test mean score in the controlled class was 61,73 and the students post-test mean score was 61,56, and the different mean score with t-test is 8,68. the significant effect was shown by students’ post-test mean score of experimental class which was treated by Mind Mapping Technique, it was greater than the students’ post-test mean score of the controlled class which was not treated by Mind Mapping. This indicate that the students score in experimental class is better and higher than controlled class. This research can be concluded that the Mind Mapping technique will give better result on students’ writing descriptive text. The Mind Mapping have positive influences and very effective in mastering writing skill especially writing descriptive text.Key Words : Mind Mapping Technique, Writing, Descriptive Text.